From the USSR to Poland. The Refugee Vicissitudes of Edward Balcerzan - Rygielska, Małgorzata (Porównania, 2025)
Edward Balerzan’s poetry volume Domysły [Guesses] (2024) includes a poem entitled Uchodźca [Refugee]. The poet, novelist, and renown literary scholar, highly sensitive to meaning, rarely resorts to using this particular word. As a man with first-hand experience of forced migration from Vovchansk in 1946, he is acutely aware of the “etymology of stigma” carried by the word (and legal term) “refugee”. But in his autobiographical stories, poetry, and scholarly reflections, he also asks questions about the aspects of the refugee experience that are individual, as well as those that are universal. I present Balcerzan’s life vicissitudes as a refugee against the background of geopolitical changes taking place in the USSR in the first half of the 20th century and a general reflection on the status and the very concept of exile. I also discuss the advantages and potential pitfalls of considering Balcerzan’s narration in the context of works by other authors “born in the USSR” as well as specific points where his account of the experience aligns or diverges from those provided by other authors.